Inverstigation of reinforcement concrete by using bamboos in the construction for low cost housing industry - Mohd Zaini Bin Othman (School of Environmental Engineering, University Malaysia Perlis, 2014)
In this research, performance of bamboos as alternative in reinforcing concrete has been evaluated. Tensile strength test of bamboos has been performed on Universal Testing Machine (UTM) to identify the yields stress of bamboos. os. From the test, the result has shown the bamboo has a similar characteristic with steel and bamboo can be as alternative for reinforcing concrete.